Enriching Teacher’s Pedagogical Strategy Using the Role of Global Competence Learning Model - Anggraeni, Anastasia Dewi (FKIP Universitas Lampung, 2019)
Enriching teachers’ pedagogical strategy using the role of global competence learning model. Objectives: The research basically aims at improving young teachers pedagogical strategies by using the role of global competence learning model. Methods: Method used in this research is descriptive qualitative with triangulation of data (observation, interview, and documentation). Findings: Implementation of global competence learning model in the learning and teaching process makes theyoung teacher will be more focus on pedagogical process and professional competence. Moreover,new cognitive skills given in the learning-teaching process as the point of enriching teachers’ pedagogicalstrategy could be achieved well. Conclusions: By the resourceful and creative learning model, theywill feel to get involved actively and will be more communicative and interactive in experiencingevery activities of learning-teaching process as well. 29 Keywords:Teachers' pedagogical strategy, learning models, global competence DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201905